Viability of Encapsulated Bacteria using Gel Particle and Foam-Mat Drying with k-carrageenan/Chitosan and i-carrageenan/Chitosan - Setijawati, Dwi; Jaziri, Abdul Aziz; Awang, Mohd Azrie Bin; Firdaus, Muhamad; Budiutami, Aryanti Diah Ayu; Alifiani, Alifiani; Mahara, Fenny Amilia; Islamy, R Adharyan (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
The study aimed to determine the effect of using a mixture of kappa-carrageenan/Chitosan and Iota carrageenan/Chitosan as encapsulating materials for Lactobacillus acidophilus and Bifidobacterium bifidum on viability, encapsulation yield, moisture content and aw of microcapsules. The research method is an experimental laboratory design, ANOVA, LSD using the Excel program. The results showed that using chitosan with a DD of 83.5% in the i-carrageenan/Chitosan mixture gave the highest viability of Bifidobacterium bifidum. The combination of i-carrageenan/chitosan coating ingredients with a concentration ratio of 0.5%:1.5% produced probiotic viability (L aci + B bifi) of 6.56 log CFU/g, while probiotic viability (B bifi) was the highest with a viability 6.70 log CFU/g. The highest probiotic encapsulation yield (L aci+B bifi) was 72.85%. The water content of the microcapsules (L aci+B bifi) was 8.96%, and the aw value was 0.63. It is recommended to carry out further testing using a processing factor for its viability.